2022
DOI: 10.1073/pnas.2204557119
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor instructs the immunomodulatory profile of a subset of Clec4a4+eosinophils unique to the small intestine

Abstract: Significance Eosinophils contribute to type 2 immunity against helminths and allergens. The small intestine harbors eosinophils with incompletely understood pathophysiological roles. Here, we show that intestinal eosinophils include two subsets. One expresses the inhibitory receptor Clec4a4 and the inhibitory ligand PD-L1 and is unique to the small intestine; the other manifests a proinflammatory phenotype. Both subsets are blood derived. Remarkably, Clec4a4 + eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…1B). SI eosinophils were further characterized by high expression of many genes involved in cholesterol biosynthesis (e.g., Hmgcs1 and Sc5d ), which corroborates a recent study highlighting de novo cholesterol biosynthesis in SI eosinophils ( 11 ) and G protein–coupled receptor signaling pathways for homomers and neurotransmitters. We further ranked the tissue-specific genes (Fig.…”
Section: Nmur1 Expression Defines a Distinctive State Of Eosinophils ...supporting
confidence: 87%
See 1 more Smart Citation
“…1B). SI eosinophils were further characterized by high expression of many genes involved in cholesterol biosynthesis (e.g., Hmgcs1 and Sc5d ), which corroborates a recent study highlighting de novo cholesterol biosynthesis in SI eosinophils ( 11 ) and G protein–coupled receptor signaling pathways for homomers and neurotransmitters. We further ranked the tissue-specific genes (Fig.…”
Section: Nmur1 Expression Defines a Distinctive State Of Eosinophils ...supporting
confidence: 87%
“…However, eosinophils are particularly abundant in the small intestine (SI) under homeostatic conditions ( 3 , 4 ), where they regulate multiple physiological processes ( 5 7 ). SI eosinophils exhibit distinctive surface proteins, transcriptional states, and signs of degranulation ( 8 11 ), which suggests that they undergo a tissue adaptation process in the SI. However, the tissue-derived cues that regulate eosinophil responses in the SI remain poorly understood.…”
mentioning
confidence: 99%
“…348 Interestingly, AHR was reported to drive the expression of immunomodulatory features such as the C-type lectin domain family 4, member a4 (Clec4a4)-a C-type lectin inhibitory receptor-and the inhibitory ligand programmed death-ligand 1 (PD-L1) in a distinct subset of blood-derived mouse eosinophils exclusively found in the lamina propria of the small intestine. 217 Moreover, different mouse eosinophil subsets were categorized as progenitors, steady state eosinophils, and type 1 and 2 activated phenotypes implying that different tissue microenvironments shape eosinophil phenotype and function. 349 In accordance, a recent study identified five eosinophil subpopulations including eosinophil precursors, immature, circulating, basal, and active eosinophils across mouse tissues based on single-cell transcriptomic profiling.…”
Section: | Sub P Opul Ationsmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that the transcription factor aryl hydrocarbon receptor (AHR) partially controls the transcriptomic changes in the process of tissue adaption of mouse intestinal eosinophils 348 . Interestingly, AHR was reported to drive the expression of immunomodulatory features such as the C‐type lectin domain family 4, member a4 (Clec4a4)—a C‐type lectin inhibitory receptor—and the inhibitory ligand programmed death‐ligand 1 (PD‐L1) in a distinct subset of blood‐derived mouse eosinophils exclusively found in the lamina propria of the small intestine 217 . Moreover, different mouse eosinophil subsets were categorized as progenitors , steady state eosinophils, and type 1 and 2 activated phenotypes implying that different tissue microenvironments shape eosinophil phenotype and function 349 .…”
Section: Subpopulationsmentioning
confidence: 99%
“…A subset of eosinophils with immunomodulatory functions was recently identified in the small intestine lamina propria of naïve mice. This population increases during aging and expresses the aryl hydrocarbon receptor and PD-L1, a ligand of the inhibitory receptor PD-1 expressed on T cells and other cell types [64,65]. In line, another recent study described a CD80 and PD-L1 expressing eosinophil population with the potential to suppress T cells that was increased during inflammatory bowel disease in mice and in a small cohort of human patients (eosinophils were defined in human as MBP + PD-L1 + cells).…”
Section: Regulation Of Granulocyte Effector Functions In Allergy and ...mentioning
confidence: 99%